CFD modeling of the combustion with detailed chemical kinetics mechanism for incompressible laminar flow - Alfaia da Cunha, Fábio (2020)
This work presents a computational fluid dynamics modeling of combustion with detailed chemical kinetics mechanism for incompressible laminar flow. In CFD modeling, the velocity field is obtained by solving the Navier-Stokes equations, the temperature field is obtained by solving an energy conservation equation, and the gas mixture composition is obtained by solving the conservation equations of individual chemical species a the GRI-MECH 3.0 reaction mechanism is used in the calculation of chemical kinetics. The numerical method for discretization of a generic conservation equation and the operator splitting technique used for the evaluation of chemical source terms are presented in detail. A computer code programmed in the Matlab language is used to simulate a test case and experimental data from a laminar diffusion flame of methane are used to validate the proposed CFD modeling of combustion.